Effect of ice mass fraction on ice slurry flow for cold energy storage application - F.A. Rayhan; Yanuar; A.S. Pamitran (Energy Reports, 2020)
The characteristics of ice slurry flows in a pipe are critical due to the potential consequence of pressure drops. This work attempted to conduct an experimental study on ice slurry flow in a horizontally posited circular pipe. This study was conducted on glycol-added (20%) ice slurry with varied ice mass fractions (10%, 15% 20%, 25%, 30%). During experiments, the flow tests were conducted by covering both laminar and turbulent flows. Results of the investigation discovered ice slurry to behave as a Newtonian fluid at mass fraction below 10%, while it also behaved as a non-Newtonian fluid at mass fraction up to 15%. Then, pressure drop was revealed to increase significantly at low-speed settings and high ice mass fractions. To maximize the use of ice slurry as a cold energy storage, therefore, ice mass fraction must be kept at below 20% in a laminar flow.
Keywords: 330; Ice slurry; Ice mass fraction; Flow; Pressure drop